The effect of exercise preconditioning with high-intensity interval training on cardiac protection following induction of myocardial infarction through mitochondrial dynamic changes in cardiac tissue in male rats - Azam Ahmadi; Majid Kashef; Hamid Rajabi; Mojtaba Salehpour (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2023)
Exercise training prevents the adverse effects of Myocardial Infarction (MI) and Ischemia/Reperfusion (I / R) and it seems that mitochondria have an important role in exercise-induced cardioprotection. So, the purpose of this study was to investigate the effects of exercise preconditioning with 4 weeks of High-Intensity Exercise Training (HIIT) on cardiac damage and mitochondrial dynamic proteins as effective factors in cardiac protection following MI. Twenty Male Wistar rats were randomly divided into 4 groups HIIT + MI, MI, HIIT, and Control. Training groups performed 4 weeks (5 days per week) of high-intensity interval training. HIIT protocol consisted of 10*1min running intervals that were separated by 2 min rest. Training intensity varied every week. For induction of myocardial infarction, a subcutaneous injection of isoproterenol was used. Creatine Kinase (CK) and lactate Dehydrogenase (LDH) were measured in serum and Drp1, and Mfn2 gene expression were measured by the real-time PCR method in the heart tissue. The results of the present study showed that CK and LDH in MI were significantly higher in HIIT + MI (p < 0.05). myocardial infarction results in a significant increase in Drp1 gene expression in the MI and HIIT + MI groups relative to the Control group. The expression of the Drp1 gene was lower in the HIIT + MI group than in the MI group, but it was not statistically significant. Also, the results demonstrated that Mfn2 was no significant difference between the groups (p > 0.05). It seems that four weeks of exercise preconditioning with HIIT training reduced injury and necrosis in cardiac tissue and can increase cardio-protection. Also, no significant effect was observed in reducing Drp1 expression due to HIIT which may indicate the need for a longer training period.